2022
DOI: 10.3389/fnins.2022.996908
|View full text |Cite
|
Sign up to set email alerts
|

Spectacles with highly aspherical lenslets for myopia control do not change visual sensitivity in automated static perimetry

Abstract: PurposeSpectacle lenses with arrays of lenslets have gained popularity in myopia control due to their high efficacy, low impact on visual performance, and non-invasiveness. One of the questions regarding their impact on visual performance that still remain is that: do the lenslets impact visual field sensitivity? The current study aims to investigate the impact of wearing spectacle lenses with highly aspherical lenslets (HAL) on the visual field sensitivity.MethodsAn automated static perimetry test (Goldman pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…After wearing the lenses for half an hour, the children learned to use the lenses to find the clear central area; thus, the influence of the peripheral lenslets was reduced. 13,26 Overall, the clear visual acuity and good visual stability of the participants provided assurance of good compliance in this longitudinal study.…”
Section: Subjective Visual Performancementioning
confidence: 78%
See 1 more Smart Citation
“…After wearing the lenses for half an hour, the children learned to use the lenses to find the clear central area; thus, the influence of the peripheral lenslets was reduced. 13,26 Overall, the clear visual acuity and good visual stability of the participants provided assurance of good compliance in this longitudinal study.…”
Section: Subjective Visual Performancementioning
confidence: 78%
“…Achieving an appropriate balance between slowing the progression of myopia and optimal visual performance is crucial in myopic children. Several clinical trials have shown that these specialized spectacle lenses have no significant impact on central visual acuity, 11 binocular visual function, 12 visual field sensitivity, 13 peripheral visual functions, 14 or peripheral motion detection. 14 However, the long-term impacts of various aspects of subjective visual performance, which are much more realistic indicators in the real visual world for evaluating multifocal lens performance, have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies that have explored the impact of myopia control lenses having a lenslet design on visual function 18‐21 . In a short‐term study, Fengchao et al 20 .…”
Section: Discussionmentioning
confidence: 99%